Cognitive Transformation Mediated By Digital 3D Sketching During Conceptual Architectural Design Process - Rahimian Leilabadi, Farzad Pour (2009)

(untitled)
To optimize the level of cognition and collaboration during conceptual architectural design phase, novice designers need to employ more flexible and intuitive digital media. This thesis studied the feasibility of using VR 3D sketching interface in order to replace current non-intuitive Computer Aided Design (CAD) tools. For this purpose a sequential mixed method research methodology including a qualitative case study research and a cognitive-based quantitative protocol analysis experiment was conducted. Foremost, it was pertinent to understand how novice designers make intuitive decisions. Hence, a case study research comprising of ethnography for data collection and artifact and protocol analysis for data analysis was employed. The purpose was to understand knowledge flow characteristics among mentors and apprentices in real-life architectural conception in studio projects. The ethnography study documented the failure of conventional sketching methods in articulating complicated design ideas. Whereas, it found that current conventional CAD tools do hinder novice designers’ creativity due to their limitation in intuitive ideation. Moreover, the subsequent artifact analysis affirmed established constructs about advantages and disadvantages of each medium in providing “solution quality” and also “certainty about correctness of solution”. The case study’s findings then became the theoretical foundations for the development of a VR 3D sketching interface for enhancing novice designers’ cognition and collaboration during the conceptual design process. This phase of study evaluated the designers’ spatial cognition at four different cognitive levels: “physical-actions”, “perceptual-actions”, “functional-actions”, and “conceptual-actions”. It also evaluated the designers’ spatial cognition in two different collaborative levels: “cognitive synchronizations” and “gestures”. The results and confirmed hypotheses showed that compared to traditional design interfaces, the utilized VR-based simple and tangible 3D sketching interface improved novice designers’ cognitive and collaborative design activities during conceptual architectural phase. In summary the thesis has evaluated inherent characteristics of the conceptual architectural design process and documented influences of current external representation tools on designers’ cognition and collaboration. It has developed the necessary theoretical foundations for cognitive and collaborative aspects of implementing VR 3D sketching interface for future implementation. Results of this thesis are limited to implementation of VR 3D sketching interface to improve cognition and collaboration during conceptual architectural design process at the novice level.In conclusion, this thesis contributes towards transforming conceptual architectural design phase from analogue to digital by proposing a new VR design interface. The author claims that this transformation can fill in the existing gap between analogue conceptual architectural design process and the remaining digital engineering parts of building design process hence enhancing the streamlining of digital design process. Finally, the author claims that the identification and documentation data on designers’ cognitive and collaborative conceptual design behaviors in the Malaysian context can be used as reference in future design studies. It is envisioned that the findings of this study can help the development of cutting-edge information technologies for design or education in the architectural field. Moreover, they will guide in the creation of future professional training programs to enhance capacity and capability of multidisciplinary professionals in using digital interfaces due to increasing global practice.